The Role of Organizational Commitment Mediates The Effect of Work-Life Balance On Organizational Citizenship Behaviour - Rihayana, I Gede (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
Organizational Citizenship Behaviour (OCB) is voluntary employee behavior outside of their formal duties that supports the organization, increases effectiveness, and creates a positive work environment without direct reward. This study aims to analyse the role of organizational commitment mediating the effect of work-life balance on organizational citizenship behaviour. Using 98 employees as the Denpasar Primary Tax Service Office. Data collection using a questionnaire and analysed using the SmartPLS 3.0 application. The results indicate that work-life balance has no significant effect on organizational citizenship behaviour, but has a significant effect on organizational commitment. Organizational commitment has a significant effect on organizational citizenship behaviour. The results of the analysis also found that organizational commitment fully mediates the effect of work life balance on organizational citizenship behavior. The implications of this study indicate the important role of organizational commitment in mediating the effect of work-life balance on organizational citizenship behaviour